ATR inhibition sensitizes HPV− and HPV+ head and neck squamous cell carcinoma to cisplatin. (August 2019) - Leonard, Brandon C.; Lee, Eliot D.; Bhola, Neil E.; Li, Hua; Sogaard, Kristian K.; Bakkenist, Christopher J.; Grandis, Jennifer R.; Johnson, Daniel E.
Highlights: ATR inhibition with AZD6738 sensitized a panel of 21 HNSCC cell line to cisplatin. AZD6738 enhanced tumor growth inhibition by cisplatin in vivo . AZD6738 enhancement of cisplatin effects was observed in both HPV − and HPV + models. Abstract: Objectives: Cisplatin is commonly used in the treatment of head and neck squamous cell carcinoma (HNSCC), and the repair of cisplatin-induced DNA damage involves activation of the DNA damage response protein ataxia telangiectasia and Rad3-related (ATR). Resistance to cisplatin therapy exacerbates adverse toxicities and is associated with poor outcomes. Since repair of cisplatin-induced DNA damage contributes to resistance, we hypothesized that inhibition of ATR using AZD6738, a well-tolerated and orally-bioavailable inhibitor, would enhance the sensitivity of HNSCC cells and tumors to cisplatin. Materials and methods: A panel of human papilloma virus-negative (HPV − ) and HPV + HNSCC cell lines were treated with cisplatin in the absence or presence of AZD6738, and effects on cell viability, colony formation, apoptosis signaling, and DNA damage were assessed. The impact of co-treatment with cisplatin plus AZD6738 on the growth of HPV − and HPV + cell line- and patient-derived xenograft tumors was also examined. Results: Inhibition of ATR with AZD6738 enhanced cisplatin-induced growth inhibition of HNSCC cell lines and tumors, in association with increased apoptosis signaling and DNA damage. Both HPV − and HPV + models were sensitized to cisplatin by ATR inhibition. Conclusion: Inhibition of ATR promotes sensitization to cisplatin in preclinical in vitro and in vivo models of HPV − and HVP + HNSCC, supporting clinical evaluation of this strategy in this disease.